A Macrofinance Model for Option Prices: A Story of Rare Economic Events - Hasler, Michael Nicolas; Jeanneret, Alexandre (Institute for Operations Research and the Management Sciences (INFORMS), 2023)
We propose a macrofinance model that rationalizes robust features in equity index option markets. When rare disasters are followed by economic recoveries, the slope of the implied volatility term structure is positive in good times but turns negative in bad times. Additionally, implied volatility decreases with moneyness in bad times (volatility skew), whereas the shape becomes a smile in good times in the presence of rare economic booms. Our theory contributes to understanding the dynamics of the implied volatility surface yet keeping standard asset-pricing moments realistic.
Keywords: macrofinance; business cycle; implied volatility; rare disasters; recoveries; booms